Effectiveness of automated writing evaluation feedback in improving english as a foreign language undergraduate students’ writing performance - Jingxin, Geng (2022)
With the rapid development of educational technology in the teaching and learning of English as a foreign language (EFL), the implementation of the automated writing evaluation (AWE) program in English writing instruction attracts researchers’ and instructors’ attention constantly in the past few decades. However, researchers of past studies have not been able to reach an agreement on the effects of the AWE in improving EFL students’ writing performance and error correction ability. Guided by the theoretical framework of Cognitive Constructivism (Graves, 1978), the concept of Zone of Proximal Development (Vygotsky, 1978) and Scaffolding (Maybin, Mercer, & Stierer, 1992) which are rooted in Sociocultural Theory (Vygotsky, 1978), and Technology Acceptance Model 3 (Venkatesh & Bala, 2008), this thesis investigated the effectiveness the AWE (Pigai) as an assisted teaching tool in improving undergraduate students’ EFL overall writing performance and analytic writing performance (i.e., content, organization, vocabulary, grammar, and mechanics) in the context of EFL undergraduate students in China. This thesis also aimed to identify student users’ acceptance toward the use of the Pigai program in college English writing course in order to triangulate the results obtained from the first two research objectives. Ninety (n=90) freshmen majoring in English were enrolled in the quasi-experimental research consisting of three non-equivalent control groups (i.e., the control group (CG) which used conventional teaching approach, the experimental group 1 (EG1) which used the process-based teaching approach (PBWA), and the experimental group 2 (EG2) which used the combination of the PBWA and the Pigai program. The results indicated that among three teaching methods, the combination of the PBWA and the Pigai (EG2) was the most effective teaching method in improving students’ overall and analytic writing performance after the intervention and the post-intervention (i.e., stopped training for a month) respectively, particularly in internalizing students’ writing knowledge in the aspects of vocabulary, grammar, and mechanics. Also, students in EG2 were able to significantly improve their error correction ability after the intervention (the combination of the PBWA and the Pigai program). Through the survey questionnaires, students in the EG2 presented a high acceptance toward the use of the Pigai program as an assisted teaching tool in general, where they noted satisfaction with the constructs of Perceived Usefulness, Perceived Ease of Use, the External Control, Output Quality, Result Demonstrability, Behavioral Intention, and Computer Self-Efficacy, with a neutral acceptance toward the construct termed Voluntariness and a negative acceptance toward the construct Perceived Enjoyment. This researcher recommends EFL language instructors, program coordinators, and other undergraduate studies stakeholders to adopt the Pigai program as an assisted teaching tool in teaching EFL writing. The researcher also suggests that during the implementation of the combination of the PBWA and the Pigai program, the instructors should inform student users of the pros and cons of the working system of the Pigai program in order to let the users make the best use of the Pigai program and introduce some meta-process strategies (i.e., screening automated feedback and using an online dictionary) to overcome its weaknesses. Future studies were recommended to explore the effectiveness of the AWE program in improving students’ writing performance by focusing on the following areas: a) establishing an instruction model of the PBWA with Chinese intrinsic characteristics; b) investigating strategies that can motivate Chinese students to provide constructive peer feedback; c) exploring strategies that students can adopt to approach the received automated feedback; d) addressing different target samples; e) utilizing qualitative designs, quantitative designs, or mixed-method designs.